Polimorfismos de BoLA-DRB3 en el bovino sintético colombiano Lucerna y asociación con conteo de células somáticas y mastitis (2006)
ABSTRACT: Previous studies have demostrated an association between BoLA-DRB3, infectious diseases and somatic cells counts in cattle. Polymorphism at the level of the microsatellite intron 2 of synthetic Bovine Colombian Lucerna was investigated. Twentyfour alleles were identified using PCR and poliacrylamide gels; their frequencies ranged from 0.02 to 0.26 among 308 individuals studied. Allele 161 was the most frequent and 159 was the least prevalent. Both subgroups mastatis affected and non affected presented similar frequencies for most alleles, indicating that the population is not in hardy Weinberg equilibrium (p< 0.05). The mean somatic cells score (log2 (CCS / 100000) + 3) for the population was 4.8(+/- 2.89). There was found a significant association between allele 191 and high somatic cell scores but not with clinical mastitis. But mastitis did present a significant association with the variables herd and number of deliveries.